A rare case of pregnancy with Sturge-Weber syndrome - Pandey, Ankita; Deshmukh, Prasad Yeshwant; Jadhav, Balaji; Nandanwar, Y. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Sturge-Weber syndrome is a rare sporadic neurocutaneous syndrome characterized by facial angiomas, ocular abnormalities (glaucoma and choroidal hemangioma), and leptomeningeal angioma. We report a case of Sturge Weber syndrome type I, associated with seizures, with gestational diabetes. She had successful labour outcome. Very few such cases have been reported in literature. The effect of pregnancy on neurological symptoms of Sturge Weber syndrome is not known.